Numerical Modeling for Corrosion Rate between Heat-affected Zone and Unaffected Base Metal of Galvanized Steel Welded by Brazing - Pinyo, Adisak; Bangyeekhan, Sompong; Yingsamphancharoen, Trinet; Rodchanarowan, Aphichart (Applied Science and Engineering Progress, 2022)
Brazing of galvanized steel causes decaying of the zinc coating and decreasing of corrosion resistance on heat-affected zone (HAZ) and weldment. The corrosion rates among the HAZ, unaffected base metal (UBM), and weldment of galvanized steel welded by brazing were numerically modeled by COMSOL Multiphysics. The numerically modeled current density values from various zones, such as the couples between the HAZ and the UBM, between the weldment and the HAZ, and between the UBM and steel were used to calculate the corrosion rates. In this work, two different methods based on Faraday’s Law, the mixed potential theory and the Numerical modeling, were compared for calculations of the corrosion rates of each region. Using the mixed potential theory, the calculated corrosion rates of regions I, II, III, IV, V and VI were 0.853, 0.284, 2.105,1.754, 2.028, and 0.554 mm/y, respectively. Where as based on the Numerical modeling, these rates of all regions were 0.918, 0.275, 2.198, 1.904, 2.151, and 0.566 mm/y, in orderly. These comparisons suggested that the corrosion rates obtained from the two methods were similar. However, the results showed that the Numerical modeling method could predict the corrosion rate with less error.